Corrosion-resistant light bicycle pedal material and preparation method thereof

Through the composite material of low molecular weight polyphenylene ether resin, transparent polystyrene resin, toughener, hollow glass microbeads and glass fiber, combined with a specific screw extrusion process, the problem of insufficient strength of bicycle pedal material is solved, and the problem of insufficient strength of bicycle pedal material is achieved. The corrosion-resistant and lightweight bicycle pedal material improves the physical performance and service life of the material.

CN119220026APending Publication Date: 2024-12-31QINGDAO GON TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411282845.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

While the existing bicycle pedal materials pursue lightweight, the strength of the materials cannot meet the usage requirements, and there are problems of waste of resources and environmental pollution.

Method used

Using composite materials with low molecular weight polyphenylene ether resin, transparent polystyrene resin, toughener, hollow glass microbeads and glass fibers, the specific screw extrusion process and additive ratio are formed to form corrosion-resistant and lightweight Quality bicycle pedal material.

Benefits of technology

It improves the toughness, strength, chemical resistance and wear resistance of the material, extends the service life of the product, and avoids the problem of increasing material density, meeting the safety and comfort needs of bicycle pedals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant light bicycle pedal material and a preparation method thereof. The material is prepared from the following components in parts by weight: 20-30 parts of low-molecular-weight polyphenyl ether resin, 25-35 parts of transparent polystyrene resin, 15-20 parts of a toughening agent, 10-15 parts of hollow glass beads, 10-15 parts of glass fibers, 2-3 parts of polytetrafluoroethylene, 0-1 part of an antioxidant, 0-1 part of a light stabilizer, 1-2 parts of an acid-binding agent and 0-1 part of other auxiliaries. The preparation method comprises the following steps: adding low-molecular-weight polyphenyl ether resin, transparent polystyrene resin, a flexibilizer, tetrafluoroethylene, an acid-binding agent, an antioxidant, a light stabilizer and other auxiliaries into a high-speed mixer according to a ratio, uniformly mixing, adding from a main feeding port of a double-side feeding twin-screw extruder, adding glass fibers from a three-area side feeding port, and carrying out extrusion molding. And hollow glass beads are added from a seventh-area side feeding port, and extrusion, water cooling and granulation are carried out. The toughness, chemical resistance, wear resistance and strength of the material are improved, and the service life of the product is effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of bicycle pedal materials, in particular to a corrosion-resistant and lightweight bicycle pedal material and a preparation method thereof. Background Art

[0002] With the popularization of cycling culture and the improvement of people's living standards, the number of people and time of outdoor cycling have greatly increased, and the public's requirements for the safety and comfort of bicycles have become higher and higher. Bicycle pedals are crucial to cycling safety and comfort.

[0003] In the prior art, pedals are most commonly made of nylon fiber-reinforced and aluminum alloy materials. The nylon fiber-reinforced material used has high physical properties but is too heavy, which runs counter to the needs of riders who pursue lightweightness. It is often replaced, resulting in waste of resources and environmental pollution. Aluminum alloy materials are expensive and difficult to process. If low-density polyphenylene ether (PPO) polystyrene (GPPS) alloy materials are used, and hydrogenated styrene-butadiene block copolymer (SEBS) is used for toughening, the toughness of the product can be improved, the material density can be further reduced, the weight of the product can be reduced, and the safety and comfort during riding can be improved. However, the weight problem of this material is solved, but the strength of the material does not meet the use requirements and cannot meet the use requirements. Summary of the invention

[0004] In order to overcome the above problems existing in the prior art, the present invention provides a method for preparing a corrosion-resistant and lightweight bicycle pedal material.

[0005] The technical solution adopted by the present invention to solve the technical problem is: a corrosion-resistant and lightweight bicycle pedal material, comprising low molecular weight polyphenylene ether resin, transparent polystyrene resin, toughening agent, hollow glass microspheres and glass fiber reinforcement system and corrosion resistance improving agent, wherein the weight percentage of each component is: 20-30 parts of low molecular weight polyphenylene ether resin, 25-35 parts of transparent polystyrene resin, 15-20 parts of toughening agent, 10-15 parts of hollow glass microspheres, 10-15 parts of glass fiber, 2-3 parts of polytetrafluoroethylene, 0-1 part of antioxidant, 0-1 part of light stabilizer, 1-2 parts of acid binding agent and 0-1 part of other auxiliary agents.

[0006] The above-mentioned corrosion-resistant and lightweight bicycle pedal material, the molecular weight range of the low molecular weight polyphenylene ether resin is 2200 to 20000, the transparent polystyrene resin is a GPPS resin polymerized from styrene monomers, and the toughening agent is a linear triblock copolymer with polystyrene as the terminal segment and ethylene-butylene copolymer obtained by hydrogenating polybutadiene as the middle elastic block.

[0007] The above-mentioned corrosion-resistant and lightweight bicycle pedal material, the hollow glass microspheres are mainly composed of borosilicate, have a density of 0.20-0.60g / cm³, a particle size of 10-250μm, and a wall thickness of 1-2μm.

[0008] The above-mentioned corrosion-resistant and lightweight bicycle pedal material, the antioxidant includes a hindered phenol main antioxidant and a secondary antioxidant, and the secondary antioxidant is one or more of a phosphite antioxidant and a thioether antioxidant.

[0009] In the above-mentioned corrosion-resistant and lightweight bicycle pedal material, the hindered phenol main antioxidant is selected from antioxidant 1010, antioxidant 1076, antioxidant 3114 and asymmetric hindered phenol antioxidant.

[0010] In the above-mentioned corrosion-resistant and lightweight bicycle pedal material, the light stabilizer is a hindered amine light stabilizer, and the acid binding agent is one or more of stearates and hydrotalcites.

[0011] The above-mentioned corrosion-resistant and lightweight bicycle pedal material, the other additives include one or more of silicones and coupling agents and one or more of lubricants and dispersants.

[0012] A method for preparing a corrosion-resistant and lightweight bicycle pedal material is used to prepare the above-mentioned corrosion-resistant and lightweight bicycle pedal material, specifically comprising: adding low molecular weight polyphenylene ether resin, transparent polystyrene resin, toughening agent, tetrafluoroethylene, acid binding agent, antioxidant, light stabilizer and other additives to a high-speed mixer in proportion and mixing them evenly, adding the mixture from the main feeding port of a double-side feeding twin-screw extruder, adding glass fiber to the third zone side feeding port, adding hollow glass microbeads to the seventh zone side feeding port, using a large lead conveying block for mixing, fully melting and mixing at 230-260°C, extruding the obtained melt through a twin-screw extruder, cooling through a water tank, and introducing it into a pelletizer for pelletizing operation to obtain the corrosion-resistant and lightweight bicycle pedal material.

[0013] The above-mentioned method for preparing a corrosion-resistant and lightweight bicycle pedal material, the thread combination from the third zone side feeding port to the seventh zone side feeding port of the twin-screw extruder is: ZME18 teeth, RKB45 / 7 / 90, RKB45 / 7 / 90, RKB45 / 7 / 90, RSE56 / 28L, RSE60 / 70, RKB45 / 7 / 90, RKB45 / 7 / 90, RKB45 / 7 / 90, RSE56 / 28L, RSE60 / 70, RSE60 / 70.

[0014] The above-mentioned method for preparing a corrosion-resistant and lightweight bicycle pedal material, the thread combination from the seven-zone side feeding port of the twin-screw extruder to the die head is: RSE90 / 90, RSE90 / 90, RSE56 / 28L, RSE90 / 90, RSE90 / 90, RSE90 / 90, RSE90 / 90, RSE90 / 90, RSE90 / 90, RSE60 / 90.

[0015] The beneficial effect of the present invention is that, compared with the prior art, the present invention adopts a system of SEBS, hollow glass microspheres, glass fibers, and polytetrafluoroethylene compounding to improve the toughness and strength of the PPO / PS alloy, thereby obtaining excellent physical properties; Compared with the prior art, the SEBS, hollow glass microspheres, glass fibers, and polytetrafluoroethylene used in the present invention can improve the chemical resistance and wear resistance of the material, effectively extending the service life of the product; Compared with the prior art, the screw combination used in the present invention adopts strong shearing from the three-zone side feeding to the seven-zone side feeding, which can fully shred and disperse the glass fibers more evenly and fully mix with other materials. The large-lead conveying block used in the seven-zone side feeding to the machine head can ensure that the glass beads are evenly mixed with other materials while reducing the breakage rate of the hollow glass beads. DETAILED DESCRIPTION

[0016] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below in conjunction with specific implementation methods.

[0017] The present embodiment discloses a corrosion-resistant, lightweight bicycle pedal material, comprising a low molecular weight polyphenylene ether resin, a transparent polystyrene resin, a toughening agent, hollow glass microspheres, a glass fiber reinforcement system, and a corrosion resistance improving agent, wherein the weight percentage of each component is: 20-30 parts of low molecular weight polyphenylene ether resin, 25-35 parts of transparent polystyrene resin, 15-20 parts of toughening agent, 10-15 parts of hollow glass microspheres, 10-15 parts of glass fiber, 2-3 parts of polytetrafluoroethylene, 0-1 part of antioxidant, 0-1 part of light stabilizer, 1-2 parts of acid binding agent, and 0-1 part of other additives.

[0018] Among them, conventional low molecular weight polyphenylene ether resin refers to one or more with a molecular weight range of 2200 to 20000, which usually has better processing performance and physical properties, such as improved thermal performance, adhesion, toughness, dimensional stability, chemical resistance, hygroscopicity and electrical properties.

[0019] Among them, transparent polystyrene resin refers to one or more GPPS resins polymerized from styrene monomer (SM), which are colorless, odorless, tasteless, shiny, and transparent particles. They are light, cheap, low in water absorption, dimensional stability, and easy to process.

[0020] Among them, the toughening agent SEBS is one or more linear triblock copolymers with polystyrene as the terminal segment and ethylene-butene copolymer obtained by hydrogenation of polybutadiene as the middle elastic block. It does not contain unsaturated double bonds, so it has good stability and aging resistance. It has both plasticity and high elasticity. It can be processed and used without vulcanization, and the scraps can be reused. It is widely used in the production of high-grade elastomers, plastic modification, adhesives, lubricant thickeners, fillers and sheath materials for wires and cables, etc. SEBS has good weather resistance, heat resistance, compression deformation resistance and excellent mechanical properties.

[0021] Among them, hollow glass microspheres, the main component of which is borosilicate, generally have a density of 0.20-0.60g / cm³, a particle size of 10~250μm, and a wall thickness of 1~2μm or more. They have the advantages of light weight, large volume, low thermal conductivity, high compressive strength, good dispersion, fluidity, and stability. In addition, they also have excellent properties such as insulation, self-lubrication, sound insulation, non-absorbent, fire-resistant, corrosion-resistant, radiation-proof, and non-toxic.

[0022] Among them, glass fiber is one or several short fibers that are easier to process. It has high tensile strength, high elastic modulus, good rigidity, large elongation within the elastic limit and high tensile strength, so it absorbs large impact energy. It is an inorganic fiber, non-flammable, good chemical resistance, low water absorption, dimensional stability, good heat resistance, and good processability. It can be made into products in different forms such as strands, bundles, felts, and fabrics. It is transparent and can transmit light, has good adhesion to resin, and is cheap.

[0023] Among them, the antioxidant is a hindered phenol main antioxidant, preferably antioxidant 1010, antioxidant 1076, antioxidant 3114 and an asymmetric hindered phenol antioxidant, and the auxiliary antioxidant is one or more of the phosphite antioxidants 168, 626, P-EPQ, 9228 and the thioether antioxidants DSTP, DSLP, 412S.

[0024] Among them, the light stabilizer is a hindered amine light stabilizer, preferably one or more of the light stabilizers UV-3808PP5, 5588, UV7303, UV770, and UV531.

[0025] The acid binding agent is one or more of stearates and hydrotalcites.

[0026] Among them, polytetrafluoroethylene is one or more polymers made by polymerizing tetrafluoroethylene as a monomer. It has excellent heat and cold resistance and can be used for a long time at -180 to 260°C. This material is resistant to acids, alkalis, and various organic solvents, and is almost insoluble in all solvents.

[0027] Among them, other auxiliary agents are selected from one or more of silicones and coupling agents, as one or more of lubricants and dispersants.

[0028] The specific preparation method and preparation process are as follows: low molecular weight polyphenylene ether resin, transparent polystyrene resin, toughening agent, tetrafluoroethylene, acid binding agent, antioxidant, light stabilizer, and other additives are added to a high-speed mixer in proportion and mixed evenly, and then the mixture is added from the main feeding port of a double-side feeding twin-screw extruder with a screw diameter of 65 mm and an aspect ratio of 44:1, glass fiber is added to the side feeding port of the third zone, and hollow glass microbeads are added to the side feeding port of the seventh zone, and a large lead conveying block is used for mixing, and the mixture is fully melted and mixed evenly at 230-260°C, and the obtained melt is extruded by a twin-screw extruder, cooled by a water tank, and introduced into a pelletizer for pelletizing operation to obtain a corrosion-resistant lightweight bicycle pedal material. The specific extrusion process is shown in Table 1.

[0029] Table 1 Extrusion process

[0030] The thread combination from the side feeding port of zone three to the side feeding port of zone seven of the twin-screw extruder is: ZME18 teeth, RKB45 / 7 / 90, RKB45 / 7 / 90, RKB45 / 7 / 90, RSE56 / 28L, RSE60 / 70, RKB45 / 7 / 90, RKB45 / 7 / 90, RKB45 / 7 / 90, RSE56 / 28L, RSE60 / 70, RSE60 / 70.

[0031] The thread combinations from the seven-zone side feeding port of the twin-screw extruder to the die head are: RSE90 / 90, RSE90 / 90, RSE56 / 28L, RSE90 / 90, RSE90 / 90, RSE90 / 90, RSE90 / 90, RSE90 / 90, RSE90 / 90, RSE60 / 90.

[0032] The above preparation method was adopted to select different component ratios to prepare the obtained lightweight bicycle pedal material, and the obtained material was subjected to performance testing. The specific component ratios of Examples 1-6 are shown in Table 2, and the specific component ratios of Comparative Examples 1-3 are shown in Table 3.

[0033] Table 2 Group ratios of Examples 1-6

[0034] Table 3 Comparative Examples 1-3 Group Allocation Ratio

[0035] The performance tests were performed on the materials obtained from Examples 1-6 and Comparative Examples 1-3. The test results are shown in Table 4.

[0036] Table 4 Performance test results of the embodiments and comparative examples

[0037] Comparing the performance results of Table 4, the hollow glass microspheres were not added to Comparative Example 1, and the density of the material increased significantly, resulting in an increase in weight while the material strength was enhanced. Glass fiber was not added to Comparative Example 2, and the Izod notched impact strength of the material was significantly reduced, that is, the rigidity of the material decreased. Glass fiber and hollow glass microspheres were not added to Comparative Example 3, and the tensile strength, flexural strength, flexural modulus, Izod notched impact strength, and thermal deformation temperature of the material were all lower than those of other embodiments, and the requirements of bicycle pedal materials for weight, strength, and rigidity could not be met. Through the above comparison, it can be seen that the ratio disclosed in this embodiment can avoid the increase in material density caused by the addition of glass fiber while using glass fiber to improve the rigidity of the material, and the addition of hollow glass microspheres can also avoid the increase in material density caused by the addition of glass fiber, which has the effect of strengthening but not increasing weight. In addition, the addition of glass fiber and glass microspheres also changes the surface roughness of the material and improves the anti-slip effect of the material.

[0038] At the same time, since polytetrafluoroethylene is added to the above materials, polytetrafluoroethylene (PTFE) has excellent chemical stability, corrosion resistance, sealing, electrical insulation and good anti-aging resistance. High temperature resistant, the working temperature is up to 250℃. Low temperature resistant, with good mechanical toughness at low temperature, even if the temperature drops to -196℃, it can maintain an elongation of 5%. Corrosion resistant, inert to most chemicals and solvents, resistant to strong acids and alkalis, water and various organic solvents. Good weather resistance, with the best aging life among plastics. Non-adhesive, it has the smallest surface tension among solid materials and does not adhere to any substance. At the same time, polytetrafluoroethylene also has the function of wear resistance, so the corrosion resistance (liquid chemical resistance) of the obtained material is good.

[0039] The above embodiments are only exemplary embodiments of the present invention and are not intended to limit the present invention. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present invention, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present invention.

Claims

1. A corrosion-resistant, lightweight bicycle pedal material, characterized in that: It includes low molecular weight polyphenylene ether resin, transparent polystyrene resin, toughening agent, hollow glass microspheres and glass fiber reinforcement system and corrosion resistance improver, and the weight percentage of each component is: 20-30 parts of low molecular weight polyphenylene ether resin, 25-35 parts of transparent polystyrene resin, 15-20 parts of toughening agent, 10-15 parts of hollow glass microspheres, 10-15 parts of glass fiber, 2-3 parts of polytetrafluoroethylene, 0-1 part of antioxidant, 0-1 part of light stabilizer, 1-2 parts of acid binding agent and 0-1 part of other additives.

2. A corrosion-resistant, lightweight bicycle pedal material according to claim 1, characterized in that: The molecular weight of the low molecular weight polyphenylene ether resin is in the range of 2200 to 20000, the transparent polystyrene resin is a GPPS resin polymerized from styrene monomers, and the toughening agent is a linear triblock copolymer with polystyrene as the terminal segment and ethylene-butylene copolymer obtained by hydrogenating polybutadiene as the middle elastic block.

3. The corrosion-resistant, lightweight bicycle pedal material according to claim 1, characterized in that: The hollow glass microspheres are mainly composed of borosilicate, have a density of 0.20-0.60 g / cm³, a particle size of 10-250 μm, and a wall thickness of 1-2 μm.

4. The corrosion-resistant, lightweight bicycle pedal material according to claim 1, characterized in that: The antioxidant includes a hindered phenol type primary antioxidant and a secondary antioxidant, wherein the secondary antioxidant is one or more of a phosphite type antioxidant and a thioether type antioxidant.

5. The corrosion-resistant, lightweight bicycle pedal material according to claim 4, characterized in that: The hindered phenol main antioxidants are selected from antioxidant 1010, antioxidant 1076, antioxidant 3114 and asymmetric hindered phenol antioxidants.

6. The corrosion-resistant, lightweight bicycle pedal material according to claim 1, characterized in that: The light stabilizer is a hindered amine light stabilizer, and the acid binding agent is one or more of stearates and hydrotalcites.

7. The corrosion-resistant, lightweight bicycle pedal material according to claim 1, characterized in that: The other auxiliary agents include one or more of silicones and coupling agents and one or more of lubricants and dispersants.

8. A method for preparing a corrosion-resistant, lightweight bicycle pedal material, characterized in that: The method is used for preparing a corrosion-resistant, lightweight bicycle pedal material as described in any one of claims 1 to 7, specifically comprising: adding low molecular weight polyphenylene ether resin, transparent polystyrene resin, toughening agent, tetrafluoroethylene, acid binding agent, antioxidant, light stabilizer and other additives in a high-speed mixer in proportion and mixing evenly, adding the mixture from the main feeding port of a double-side feeding twin-screw extruder, adding glass fiber to the third zone side feeding port, adding hollow glass microbeads to the seventh zone side feeding port, mixing using a large lead conveying block, fully melting and mixing at 230-260° C., extruding the obtained melt through a twin-screw extruder, cooling through a water tank, and introducing it into a pelletizer for pelletizing operation to obtain the corrosion-resistant lightweight bicycle pedal material.

9. The method for preparing a corrosion-resistant and lightweight bicycle pedal material according to claim 8, characterized in that: The thread combination from the third zone side feeding port to the seventh zone side feeding port of the twin-screw extruder is: ZME18 teeth, RKB45 / 7 / 90, RKB45 / 7 / 90, RKB45 / 7 / 90, RSE56 / 28L, RSE60 / 70, RKB45 / 7 / 90, RKB45 / 7 / 90, RKB45 / 7 / 90, RSE56 / 28L, RSE60 / 70, RSE60 / 70.

10. The method for preparing a corrosion-resistant and lightweight bicycle pedal material according to claim 8, characterized in that: The thread combinations from the seven-zone side feeding port to the die head of the twin-screw extruder are: RSE90 / 90, RSE90 / 90, RSE56 / 28L, RSE90 / 90, RSE90 / 90, RSE90 / 90, RSE90 / 90, RSE90 / 90, RSE90 / 90, RSE60 / 90.